Cannabinoid receptors expression in bone marrow trephine biopsy of chronic lymphocytic leukaemia patients treated with purine analogues - Piszcz, J.A.; Lemancewicz, D.; Kloczko, J.; Dzieciol, J.; Rusak, M.; Dabrowska, M. (Experimental Oncology, 2007)
Background: Cannabinoid receptors CB1 and CB2 are part the endocannabinoid system that plays an important role in the process of proliferation and apoptosis of different neoplastic cells. B-cell chronic lymphocytic leukaemia is one of the diseases in which these processes are altered. Aim: The aim of our study was the assessment of cannabinoid receptor expression on the B-lymphocytes in bone marrow trephine biopsy from leukaemic patients at diagnosis and after purine analogue treatment. Methods: The biopsy was taken routinely and standard immunohistochemical staining procedure for paraffin embedded sections was applied. The cannabinoid receptors were detected using specific primary polyclonal antibody anti-CB1 and anti-CB2. Additionally, an existence of cannabinoid receptors was confirmed by flow cytometry. Results: The results showed that the expression of CB1 receptor on the surface of neoplastic cells was lower than that of CB2 (17.0 ± 3.1% and 92.1 ± 1.7% respectively, p < 0.001). Nine of the patients responded to applied treatment with a reduction in leukaemic infiltration (77.2 ± 6.9% to 30.2 ± 6.5%, p = 0.007) and CB1 receptor expression (24.4 ± 4.8% to 8.6 ± 2.9%, p = 0.01), but there was no change in CB2 expression (91.7 ± 2.7% vs 90.9 ± 2.8%, p = 0.69). Four patients without remission expressed even greater number of the receptors. In all of the cases both cannabinoid receptor types antibodies gave positive reaction. Furthermore, the existence of cannabinoid receptors on neoplastic lymphocytes was confirmed by flow cytometry. Conclusion: The study provides original evidence for the existence of cannabinoid receptors on B-lymphocytes in chronic lymphocytic leukaemia patients. The receptors are thought to be a new structure that can modify the course of the disease and may be considered as a new target in leukaemia treatment. Обоснование: рецепторы каннабиноидов CB1 и CB2 яв ляются частью системы эндоканнабиноидов, которая играет важную
роль в процессах пролиферации и апоптоза различных неопластических клеток. Одним из заболеваний, при которых происходит
нарушение этих процессов, является В-клеточный хронический лимфлейкоз. Цель: оценка экспрессии рецепторов
каннабиноидов на В-лимфоцитах в трепанобиоптатах у больных лейкозом до и после проведения лечения с использованием
пуриновых аналогов. Методы: биоптаты получили рутинными методами; иммуногистохимическое исследование депарафинизированных
срезов проводили по стандартной процедуре. Рецепторы каннабиноидов определяли с использованием
специфических моноклональных антител анти-CB1 и анти-CB2. Кроме того, наличие рецепторов подтверждено при по-
мощи проточной цитофлуориметрии. Результаты: показано, что экспрессия рецептора CB1 на поверхности опухолевых
клеток ниже, чем экспрессия CB2 (17,0  ± 3,1% и 92,1 1,7% твенно, p < 0,001). После проведенного лечения
у 9 пациентов отмечалось уменьшение лейкозного инфильтрата (77,2 6,9% до 30,2 6,5%, p = 0,007) и снижение экспрессии
рецептора CB1 (24,4 4,8% до 8,6 2,9%, p = 0,01), однако различий в экспрессии CB2 не отмечали (91,7
2,7% против 90,9 2,8%, p = 0,69). У 4 пациентов, у которых не удалось достичь ремиссии, определяли даже повышение
экспрессии рецепторов. Во всех случаях маркировки антителами к обоим типам рецепторов каннабиноидов отмечали поло-
жительную реакцию. Более того, присутствие рецепторов каннабиноидов на злокачественных клетках подтверждали при
помощи проточной цитометрии. Выводы: в ходе исследования показано изначальное наличие рецепторов каннабиноидов
на В-лимфоцитах у больных хроническим лимфолейкозом. Указанные рецепторы могут быть новой структурой, которая
может быть модифицирована в течение болезни, и могут считаться новой мишенью при лечении больных лейкозом.